GIS Based Application in Education for Aurangabad city (International Journal of Engineering and Computer Science, 2016)
Education is the basic fundamental of any country. The purpose of this paper is to examine the different categories of schools inAurangabad city, Maharashtra, India. It checks the compatibility of GIS with education facilities. We classified four different categories ofschools in Aurangabad city, mapped them using Google Earth and KML. The categories of schools are classified on medium of the schools.We traced these all schools with their exact longitude and latitude and detail information about the particular school is also shown usingGoogle Earth API. In this paper some management levels are used by assigning some random points anywhere in Aurangabad city. Due tothat people get the best schools information from that random point which is nearer. We have assigned some ranking to the schoolsaccording to their facilities, infrastructure, admission status, outcome etc. So the people can see covered area about the particular schooland area where actual schools are required.